Variations of biochemical parameters along a transect in the Southern Ocean, with special emphasis on volatile halogenated organic compounds - Abrahamsson, Katarina; Bertilsson, S; Chierici, Melissa; Fransson, Agneta; Froneman, P. W; Lorén, Anders; Pakhomov, E. A. (Deep Sea Research Part II: Topical Studies in Oceanography, 2004)
A number of parameters of biogeochemical interest were monitored along a north-southerly transect (S 43-S 63degrees) in the Atlantic Sector of the Southern Ocean from the 8th to the 20th of December 1997. Changes in total dissolved inorganic carbon (C-T) and total alkalinity (A(T)) were mostly dependent on temperature and salinity until the ice edge was reached. After this point only a weak correlation was seen between these. Highest mean values of C-T and A(T) were observed in the Winter Ice Edge (WIE) (2195 and 2319 mumol kg(-1), respectively). Lowest mean AT (2277 mumol kg(-1)) was observed in the Sub-Antarctic Front (SAF), whereas lowest mean CT concentration (2068 mumol kg(-1)) was associated with the Sub-Tropical Front (STF). The pH in situ varied between 8.060 and 8.156 where the highest values were observed in the southern part of the Antarctic Polar Front (APF) and in the Summer Ice Edge (SIE) Region. These peaks were associated with areas of high chlorophyll a (chl a) and tribromomethane values. In the other areas the pH in situ was mainly dependent on hydrography. Bacterial abundance decreased more than one order of magnitude when going from north to south. The decrease appeared to be strongly related to water temperature and there were no elevated abundances at frontal zones. Microphytoplankton dominated in the SAF and APF, whereas the nano- and picoplankton dominated outside these regions. Volatile halogenated compounds were found to vary both with regions, and with daylight. For the iodinated compounds, the highest concentrations were found north of the STF. Brominated hydrocarbons had high concentrations in the STF, but elevated concentrations were also found in the APF and SIE regions. No obvious correlation could be found between the occurrence of individual halocarbons and chl a. On some occasions trichloroethene and tribromomethane related to the presence of nano- and microplankton, respectively.